Investigating the implementation of infection prevention and control practices in neonatal care across country income levels: a systematic review - Emanuela Nyantakyi; Julia Baenziger; Laura Caci; Kathrin Blum; Aline Wolfensberger; Angela Dramowski; Bianca Albers; Marta Castro; Marie-Therese Schultes; Lauren Clack (Antimicrobial Resistance and Infection Control)
Abstract Background Despite the proven effectiveness of infection prevention and control (IPC) practices in reducing healthcare-associated infections and related costs, their implementation poses a challenge in neonatal care settings across high-income (HICs) and low- and middle-income countries (LMICs). While existing research has predominantly focused on assessing the clinical effectiveness of these practices in neonatal care, aspects concerning their implementation remain underexplored. This systematic review therefore aimed to analyze implementation determinants and employed strategies for implementing IPC practices in inpatient neonatal care across country income levels. Methods Following a targeted search in seven databases, titles and abstracts as well as full texts were screened in a dual review process to identify studies focusing on the implementation of IPC practices in inpatient neonatal care and reporting on implementation determinants and/or implementation strategies. Implementation determinants were synthesized using the updated Consolidated Framework for Implementation Research. Implementation strategies were coded according to the Expert Recommendations for Implementing Change taxonomy. A convergent integrated approach was used to narratively summarize results across qualitative and quantitative studies. χ 2 Tests and Fisher’s Exact Tests were performed to analyze differences in implementation determinants and strategies across IPC practices and country income levels. The quality of included studies was assessed using the Mixed Methods Appraisal Tool. Results Out of 6,426 records, a total of 156 studies were included in the systematic review. Neonatal units in LMICs and HICs showed general commonalities in reported implementation determinants, which were mainly reported at the organizational level. While educational as well as evaluative and iterative strategies were most frequently employed to support the implementation of IPC practices in both LMICs and HICs, other strategies employed showed variance across country income levels. Notably, the statistical analyses identified a significant association between country income levels and implementation determinants and strategies respectively ( $$\:ρ\:$$ <0.05). Conclusion The results of this systematic review underscore the importance of the organizational level for the implementation of IPC practices in neonatal care irrespective of country income level. However, further research is needed to understand the underlying relationships of factors and dynamics contributing to the observed practice variances in LMICs and HICs. Registration PROSPERO (CRD42022380379).